THE IMPLEMENTATION OF HISTORY EDUCATION AT KENDRIYA VIDYALAYA SENIOR SECONDARY SCHOOL: A STUDY OF CURRICULUM AND PEDAGOGICAL PRACTICES - Rajkamal.D (CV. Fahr Publishing, 2025)
This study explores the implementation of history education at Kendriya Vidyalaya No. 2, New Delhi, with the aim of understanding how national curriculum guidelines are translated into classroom practices. The research investigates the pedagogical strategies employed by history teachers, the extent of student engagement, and the challenges faced in delivering inclusive and critical historical content. Using a qualitative case study approach, data were collected through classroom observations, semi-structured interviews with four history teachers and eight students, and document analysis of teaching materials and lesson plans. Findings reveal that history teaching remains largely textbook-driven and exam-oriented, with minimal use of interactive methods such as group discussions, debates, or inquiry-based learning. Sensitive topics like caste, colonialism, and partition are often avoided or presented superficially, limiting students’ exposure to diverse historical perspectives. Teachers cited institutional constraints, curriculum load, and political sensitivity as factors influencing their teaching choices. Student responses indicated a general disinterest in history, stemming from its perceived irrelevance and passive delivery. The novelty of this research lies in its focus on the micro-level dynamics of classroom practice, rather than textbook content or curriculum policy alone. It applies critical pedagogy and postcolonial theory to analyze how historical narratives are shaped and constrained in practice. The study contributes to global debates on decolonizing education and emphasizes the importance of teacher agency and pedagogical reform. In conclusion, enhancing professional development and promoting reflective teaching practices are essential to making history education more meaningful and socially responsive.